DECISION SUPPORT SYSTEM STUDENT ACHIEVEMENT DURING THE COVID-19 PANDEMIC WITH METHOD FUZZYANALYTIC HIERARCHY PROCESS - Anita Rahayu; Dudih Gustian (Jurnal Teknik Informatika (Jutif), 2022)
Achievement is the result of a measurable and scheduled learning process within a certain time. Therefore, this achievement becomes a benchmark for the success of a learning process, especially for students who are used as reflections for improvement to get better. However, since the Covid-19 outbreak, all students have carried out online teaching and learning activities from home, this is certainly a problem for every student. So that face-to-face learning is hampered, the online method is not effective, it has an impact on the decline in student achievement at SDN Cisarua 01. The results of field observations found that the students' semester exam results were on average unsatisfactory and inversely proportional to the results of the assignments done. the students at home satisfactorily. The Fuzzy Analytical hierarchy process (FAHP) method is used in this second phase of research in order to reduce the ranking of the same value from phase one with the Analytical hierarchy process (AHP) method, so as to increase the accuracy of the weighting of the method used. The criteria used in the study to improve student achievement are the criteria for parental support, facilities, environment and school. The Fuzzy Analytical Hierarchy Process (FAHP) method is able to provide a solution in reducing the ranking process which has the same value as the percentage obtained by 68% and the percentage of unequal ranking 32%. This research is able to help the school take a decision to overcome the decline in student achievement. So that it can have an impact on the school in determining ranking decisions to overcome the decline in student achievement.